KAJIAN LITERATUR PEMBELAJARAN KONSEP PENGUKURAN PANJANG, BERAT, WAKTU, DAN VOLUME KUBUS SERTA BALOK DENGAN PEMANFAATAN MEDIA KONKRET DI SD - Fat-thahillah Candra At-Toriq; Fingka Wahyu Anggraini; Dimas Raskian Aji; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning mathematics in elementary school requires a strong conceptual understanding, particularly in measurement topics such as length, weight, time, and the volume of cubes and rectangular prisms, which are often perceived as abstract by students. This study aims to review and analyze previous research related to the use of concrete media in teaching measurement concepts in elementary schools. This research employed a literature review method by collecting and examining relevant articles from accredited national journals and reputable online journals. The data were analyzed using a descriptive qualitative approach to identify patterns, similarities, and differences in research findings. The results of the literature review indicate that the use of concrete media, such as measuring tools, unit ladders, Smartbox, Boxes Paper, unit cubes, and other manipulatives, has a positive impact on students’ conceptual understanding, learning engagement, and learning outcomes. Concrete media are effective in helping students understand measurement concepts in a meaningful way, particularly for length and weight, while studies on volume measurement remain limited but show promising results through the use of manipulatives. Therefore, the integration of concrete media in mathematics instruction is strongly recommended to enhance the effectiveness of measurement learning in elementary schools. Keywords: Concrete Media, Measurement Concepts, Mathematics Learning